2018
DOI: 10.1007/s00247-018-4128-6
|View full text |Cite
|
Sign up to set email alerts
|

Occult head injury is common in children with concern for physical abuse

Abstract: Our results show a high prevalence of occult head injury in patients <2 years old with suspected physical abuse. Our data support the ACR recommendation that clinicians should have a low threshold to perform neuroimaging in patients <2 years of age.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

1
15
0

Year Published

2019
2019
2024
2024

Publication Types

Select...
7
1

Relationship

1
7

Authors

Journals

citations
Cited by 24 publications
(16 citation statements)
references
References 26 publications
1
15
0
Order By: Relevance
“…In determining occult injuries, our study classified patients with any skull fracture seen on X-ray as having a sign of head injury, regardless of whether the CT head scan or skeletal survey were carried out first. However, other published studies [7][8][9][10][11][12] variably include skull fractures as occult head injuries, and If an intracranial injury is associated with the skull fracture, this would be counted as an occult intracranial injury. In addition, our study did not attempt to ascertain extracranial injuries, as their clinical and forensic value can be difficult to determine.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…In determining occult injuries, our study classified patients with any skull fracture seen on X-ray as having a sign of head injury, regardless of whether the CT head scan or skeletal survey were carried out first. However, other published studies [7][8][9][10][11][12] variably include skull fractures as occult head injuries, and If an intracranial injury is associated with the skull fracture, this would be counted as an occult intracranial injury. In addition, our study did not attempt to ascertain extracranial injuries, as their clinical and forensic value can be difficult to determine.…”
Section: Discussionmentioning
confidence: 99%
“…[6] Studies reporting frequency of occult head injuries in infants with suspected physical abuse differ in their definition of occult and in populations studied, with reported yields ranging from 4% to 38%. [7][8][9][10][11][12] Information about yield is important in balancing risks and benefits of medical investigations. The Royal College of Paediatrics and Child Health calls for 'further research… to determine the positive diagnostic yield of head CT in children less than one year of age'.…”
Section: Introductionmentioning
confidence: 99%
“…Rarely, radionuclide imaging (‘bone scan’) may be indicated although this is now usually replaced by a second skeletal survey 1 2 4. Because of the risk of intracranial injuries, it is recommended best practice routinely to include a non-contrast CT scan of the head in children under 1 year1 5 and to have a low threshold for neuroimaging in children under 2 years where abuse is suspected 2 6…”
Section: Introductionmentioning
confidence: 99%
“…Despite the fact that both the incidences of ICI and abuse-related fracture are highest in very young children, few studies have examined the co-occurrence of ICI and abuse-related LBF (13,(16)(17)(18). Maguire et al estimated the probability of ICI in hospitalized children with head trauma and reported that LBF alone has a 35% positive predictive value for ICI (19).…”
Section: Introductionmentioning
confidence: 99%
“…Despite the fact that both the incidences of ICI and abuse-related fracture are highest in very young children, few studies have examined the co-occurrence of ICI and abuse-related LBF ( 13 , 16 , 17 , 18 ). Maguire et al.…”
Section: Introductionmentioning
confidence: 99%